Cytotoxic substituted indolizines as new colchicine site tubulin polymerisation inhibitors - Monica-Cornelia Sardaru; Anda Mihaela Craciun; Cristina-Maria Al Matarneh; Isabela Andreea Sandu; Roxana Maria Amarandi; Lacramioara Popovici; Catalina Ionica Ciobanu; Dragos Peptanariu; Mariana Pinteala; Ionel I. Mangalagiu; Ramona Danac (Taylor & Francis Group, 2020)
A potential microtubule destabilising series of new indolizine derivatives was synthesised and tested for their anticancer activity against a panel of 60 human cancer cell lines. Compounds 11a, 11b, 15a, and 15j showed a broad spectrum of growth inhibitory activity against cancer cell lines representing leukaemia, melanoma and cancer of lung, colon, central nervous system, ovary, kidney, breast, and prostate. Among them, compound 11a was distinguishable by its excellent cytostatic activity, showing GI50 values in the range of 10-100 nM on 43 cell lines. The less potent compounds 15a and 15j in terms of GI50 values showed a high cytotoxic effect against tested colon cancer, CNS cancer, renal cancer and melanoma cell lines and only on few cell lines from other types of cancer. In vitro assaying revealed tubulin polymerisation inhibition by all active compounds. Molecular docking showed good complementarity of active compounds with the colchicine binding site of tubulin.